PERBANDINGAN KEDUDUKAN DAN KEWENANGAN KEPOLISIAN DALAM KONSTITUSI YANG PERNAH BERLAKU DI INDONESIA - Surbakti, Farrel Eden; Abdilah, Ali (Jurnal Hukum & Pembangunan, 2021)
The police are defined as a tool of the state in charge of maintaining the security and order of the community, providing protection, and providing protection to the public. The relationship between the community and the police themselves is mutually influencing, where the existence of the police is functional in the structure of life. When people experience changes due to various factors, then there is also a change in moral standards that result in order and order of life according to previous cultures are no longer used. This is what causes the role and function of the police must always adjust. The police are referred to as determining concretely what is called order enforcement. The importance of the existence of police institutions in Indonesia has become generally accepted. But regarding the position of the police institute in the Indonesian constitutional arrangement is still a problem. With the constitution changing from the era of independence to the era of reform, the position of the police in the constitutional arrangement has changed.